Altered brain structural topological properties in Parkinson's disease with levodopa-induced dyskinesias. (October 2019) - Wang, Lina; Wang, Min; Si, Qianqian; Yuan, Yongsheng; Ma, Kewei; Gan, Caiting; Zhang, Kezhong
Abstract: Objectives: In this study, the alterations of structural topological properties in Parkinson's disease (PD) patients with levodopa-induced dyskinesias (LIDs) were explored using white matter structural network connectome derived from diffusion tensor imaging (DTI). Methods: 21 dyskinetic PD patients, 21 non-dyskinetic PD patients and 25 healthy controls were studied in global and nodal topological properties of structural networks after controlling age, gender and education. Afterwards, post hoc analyses were performed to explore further differences. Finally, multiple linear regression analysis was employed to test the associations between significant different properties and the severity of dyskinesias in PD. Results: Dyskinetic PD patients exhibited significant increased global efficiency, local efficiency, clustering coefficient, but decreased shortest path length compared with the non-dyskinetic. Additionally, increased nodal efficiency in bilateral inferior frontal gyrus (IFG), right putamen, right thalamus, and decreased nodal shortest path length in bilateral IFG and right thalamus, were discovered in dyskinetic PD in comparison with non-dyskinetic PD. Notably, a negative correlation between the Abnormal Involuntary Movement Scale (AIMS) scores and shortest path length of whole-brain network was found in PD with LIDs. Conclusions: Our results indicated excessively optimized topological organization of whole-brain structural connectome in PD patients with LIDs. These findings also illustrated that excessively strengthened basal ganglia-thalamocortical nodal structural connections played an important role in the presence of LIDs. Highlights: PD patients with LIDs exhibited excessively optimized topological organization of whole-brain structural connectome. Excessively strengthened basal ganglia-thalamocortical nodal structural connections affected the presence of LIDs. Altered global property was correlated with the severity of dyskinesias in PD.